Reinforced ultra-lightweight cement composite flat slabs: Experiments and analysis. (5th April 2016) - Yan, Jia-Bao; Wang, Jun-Yan; Richard Liew, J.Y.; Qian, Xudong; Zhang, Wei
Abstract: Novel lightweight flat slabs made of ultra-lightweight cement composite (ULCC) with density of 1329–1649 kg/m 3 and strength of 52.0–87.3 MPa have been developed for buildings and offshore constructions. This paper studied the structural behaviors of the reinforced ULCC flat slabs under concentrated loading through a 14-specimen test program. The test program aimed to investigate the influences of shear span, flexural reinforcing ratio, depth of the section, and volume fraction of fibers on the failure mode, load deflection behaviors, and punching shear resistances of the ULCC flat slabs. Analytical models on predicting the tensile versus compressive strength relationships of ULCC were developed through regression analysis on 102 test data, and this developed relationship was then used to develop analytical models on punching shear resistance of ULCC flat slabs. Analytical models were developed to predict the punching shear resistance of the ULCC flat slabs through modifying the code provisions. The accuracy of these developed models was confirmed through validations against the reported test results. Graphical abstract: Highlights: Using ULCC material to make novel lightweight flat slabs for constructions The novel lightweight flat slabs reduce 40% self-weight of structures. New equations predict well on tensile–compressive strength relationship of ULCC. New equations predict well on punching shear resistance of the lightweight slabs.